The Essential Oil from the Resurrection Plant Myrothamnus moschatus Is Effective against Arthropods of Agricultural and Medical Interest - Roman Pavela; Marta Ferrati; Eleonora Spinozzi; Filippo Maggi; Riccardo Petrelli; Rianasoambolanoro Rakotosaona; Renato Ricciardi; Giovanni Benelli (MDPI AG, 2022)
This work aimed to evaluate the chemical composition, insecticidal and acaricidal potential of the essential oil (EO) obtained from the resurrection plant Myrothamnus moschatus (Baill.) Baill. (Myrothamnaceae) from Madagascar. The EO bioactivity was evaluated against selected arthropod pests and vectors of agricultural and public health relevance. The most abundant volatile compounds were trans-pinocarveol (37.7 ± 4.2%) and pinocarvone (20.8 ± 3.1%), similar to the EO of the chemotype collected from the same region. Lethal concentrations (LC50) or doses (LD50) from acute toxicity tests were estimated for Musca domestica (L.) adults at 22.7 µg adult−1, for Spodoptera littoralis (Boisduval) larvae at 35.6 µg larva−1, for Culex quinquefasciatus (Say) at 43.6 µg mL−1, for adults of Metopolophium dirhodum (Walker) at 2.4 mL L−1, and for adults of Tetranychus urticae (Koch) at 1.2 mL L−1. The good insecticidal and acaricidal activities determined in this work may open a new perspective on the use of this plant as a source of botanical insecticide ingredients. The exploitation of this species could also be important for the African economy, helping local farmers cultivating this plant.